2022
DOI: 10.3390/cancers14164037
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Vaccines: A Promising Approach in the Fight against Ovarian Cancer

Abstract: Ovarian cancer (OC) is the deadliest gynecological malignancy in developed countries and is the seventh-highest cause of death in women diagnosed with cancer worldwide. Currently, several therapies are in use against OC, including debulking surgery, chemotherapy, as well as targeted therapies. Even though the current standard-of-care therapies improve survival, a vast majority of OC patients relapse. Additionally, immunotherapies have only resulted in meager patient outcomes, potentially owing to the intricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 165 publications
(282 reference statements)
0
10
0
Order By: Relevance
“…For instance, mature pDCs exert immunostimulatory function, which is characterized by the production of large amounts of type I IFNs. Whereas, in the TME, pDCs with reduced production of type I IFNs favor the development of Treg cell, exert immunosuppressive effects on CTLs and promote tumor progression ( 8 , 9 , 120 , 121 ). Several studies have indicated a role for IRF4 in development of monocytes, pDCs, and cDCs ( 122 124 ).…”
Section: Regulation Of Irf4 In Immunosuppressive Cells In the Tmementioning
confidence: 99%
“…For instance, mature pDCs exert immunostimulatory function, which is characterized by the production of large amounts of type I IFNs. Whereas, in the TME, pDCs with reduced production of type I IFNs favor the development of Treg cell, exert immunosuppressive effects on CTLs and promote tumor progression ( 8 , 9 , 120 , 121 ). Several studies have indicated a role for IRF4 in development of monocytes, pDCs, and cDCs ( 122 124 ).…”
Section: Regulation Of Irf4 In Immunosuppressive Cells In the Tmementioning
confidence: 99%
“…At present, there are several therapies for OC, including tumor resection, chemotherapy and targeted therapy. Although there has been some progress in various new treatments, about 80-85% of patients with advanced stage still relapse [15]. Some researchers explored the clinical efficacy of DC vaccine in ovarian cancer.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Another strategy involves utilizing autologous dendritic cells activated through exposure to tumor-associated antigens, along with enhancing the cellular response through exposure to adjuvant molecules (see Figure 2 ) [ 6 , 7 ]. Dendritic cells, serving as antigen-presenting cells, are inoculated autologously and activated, mirroring the approach seen with Sipuleucel-T, an approved therapy for metastatic prostate cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%